2006
DOI: 10.1554/05-647.1
|View full text |Cite
|
Sign up to set email alerts
|

Faster Lizards Sire More Offspring: Sexual Selection on Whole-Animal Performance

Abstract: Sexual selection operates by acting on variation in mating success. However, since selection acts on whole-organism manifestations (i.e., performance) of underlying morphological traits, tests for phenotypic effects of sexual selection should consider whole-animal performance as a substrate for sexual selection. Previous studies have revealed positive relationships between performance and survival, that is, natural selection, but none have explicitly tested whether performance may influence reproductive succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 70 publications
4
78
2
Order By: Relevance
“…Indeed, the relationships between jumping and fitness and testis morphology and fitness have yet to be empirically determined in this species. Nonetheless, a decline in fitness due to reduced locomotory ability is consistent with findings from previous studies investigating the evolutionary and ecological relevance of whole-organism performance in other vertebrate species (e.g., Husak et al 2006;Phillips et al 2006). Our data suggest that future studies measuring the form and intensity of selection acting on jumping performance in L. pipiens over longer time periods would be valuable for understanding the impact of such infections on evolutionary trajectories in this species.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, the relationships between jumping and fitness and testis morphology and fitness have yet to be empirically determined in this species. Nonetheless, a decline in fitness due to reduced locomotory ability is consistent with findings from previous studies investigating the evolutionary and ecological relevance of whole-organism performance in other vertebrate species (e.g., Husak et al 2006;Phillips et al 2006). Our data suggest that future studies measuring the form and intensity of selection acting on jumping performance in L. pipiens over longer time periods would be valuable for understanding the impact of such infections on evolutionary trajectories in this species.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast with our study, several previous studies have found greater locomotor performance to be positively associated with social dominance (Garland et al, 1990;Hews, 1990;Robson and Miles, 2000;Lailvaux et al, 2004;Perry et al, 2004;Husak et al, 2006a;Peterson and Husak, 2006;Hall et al, 2010). However, a study by Huyghe et al, (2005), found no correlation between locomotor performance and dominance, but rather between increased bite force capacity and dominance (Huyghe et al, 2005).…”
contrasting
confidence: 99%
“…Several studies have demonstrated sexual selection targets whole-organism performance such as locomotor and fighting capacities, that are often used during territorial disputes and other male-male agonistic interactions (Husak et al, 2006a;Husak et al, 2006b;Irschick et al, 2007). These studies have established that males and females frequently differ in whole-organism performance, as they do in sexually dimorphic traits (Cullum, 1998;Lailvaux et al, 2003;Krasnov et al, 2004).…”
Section: Sexual Selection and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Reilly, 2013;) because many ecologically relevant activities, such as escaping from predators, foraging and searching for reproductive partners, depend on locomotion (Meylan and Clobert, 2004;Husak et al, 2006). Therefore, locomotor performance has been widely regarded as probably associated with fitness (Christian and Tracy, 1981;Garland, 1999).…”
Section: Introductionmentioning
confidence: 99%